Hybrid Composite of Biomass-Derived Activated Carbon and Mg/Al Hydrotalcite for Caffeine Adsorption from Aqueous Solutions - Estin Nofiyanti; Noer Laelly Barorroh Taufik Abdul Ghofur; Dian Utami (Jurnal Teknik Kimia dan Lingkungan, 2026)
This study investigated the adsorption performance of activated carbon (AC) derived from jengkol (Pithecellobium jiringa) peel and its composites with Mg/Al hydrotalcite (HT) for caffeine removal from aqueous solutions. The adsorbents were characterized using FTIR, XRD, and SEM-EDX, confirming the presence of –OH groups, M–O–M bonding, and layered porous morphology. Batch adsorption experiments evaluated the effects of contact time, pH, and initial concentration. AC showed the highest removal efficiency (96.44% at 3 ppm), while ACHT 12 demonstrated stable performance at moderate concentrations and fit well to the Langmuir isotherm (R2 = 0.9609) and pseudo-second-order kinetics (R2 = 0.9912). ACHT 21 followed the Freundlich model (R2 = 0.7758), indicating heterogeneous multilayer adsorption. Optimal adsorption occurred in acidic conditions (pH 3–5), which reflects the characteristics of pharmaceutical wastewater. The results confirm the potential of jengkol-based adsorbents as low-cost, sustainable alternatives for caffeine-contaminated water treatment.